PELAKSANAAN PENYIDIKAN TINDAK PIDANA PENCURIAN DENGAN PEMERIKSAAN ACARA CEPAT PADA SATUAN RESERSE KRIMINAL KEPOLISIAN RESOR KOTA PADANG - Khairani, Elmarisa; Wibowo, Adhi (UNES Journal of Swara Justisia, 2019)
Crime of theft that has a loss value of under two million five hundred rupiahbased on Article 1 and Article 2 of the Supreme Court Regulation Number 2 of 2012concerning Adjustment of Light Tipring and the Amount of Fines in the Criminal Codequalify as a misdemeanor. As a misdemeanor, the investigation and trial process iscarried out with a quick event. However, in practice, problems and constraints faced bylaw enforcement officers who are members of the criminal justice system arise,especially the police as investigators who are authorized by law to implement theprovisions of the Regulation as happened in the investigation of criminal cases of theftin the Resort Police Criminal Investigation Unit Padang City.